Multiterminal Impedanse-Based Fault Location through Synchronized Phasor Measurements - Yablokov, A.A.; Tychkin, A.R.; Ivanov, I.E. (International Youth Scientific and Technical Conference on Relay Protection and Automation (Online), 2023)
Switching off an overhead transmission line can have a dramatic impact on the electric power system: interruption of power transmission, increasing the loading of adjacent power grid components, loss of load supply, islanding, etc. Improving the accuracy of transmission line fault location (FL) is a key aspect to restore the line back in service as soon as possible. Impedance-based FL is implemented with power system quantities measured under fault conditions and put into closed-form expressions, specialized tables or simulation models. Software for FL [ 1 - 3 ] utilizes either single-end or two-end current and voltage measurements obtained from digital fault recorders (DFRs) or digital relays with a FL function. The FL error relative to the line length can sometimes be greater than 10% as a consequence of various uncertainties such as a fault resistance (for single-end FL methods), loss of good-quality synchronization (for two-end expressions), current transformer (CT) saturation [4] , incorrect transmission line data, and so on. Some of these issues may be tackled by employing measurements captured at other points in a grid, outside of the faulty line. However, there are no clear rules and unique protocols to transmit data from DFRs and relays for FL (especially in a real-time environment). Also, the DFRs are not necessarily synchronized via GPS/GLONASS and similar precise time sources, which creates a need for "post" -synchronization of measurements recorded under a line fault.